PERANCANGAN SISTEM DISTRIBUSI ZONA II TANJUNG BALAI KARIMUN KEPULAUAN RIAU - Ivan Cahya Raswoko; Syamsir Abduh; Maula Sukmawidjaja (President University, 2019)
The distribution system is one of the most important elements to be able to distribute electrical energy from power plants to consumers. Tanjung Balai Karimun, Kepulauan Riau is an island near the island of Batam. PT Karimun Power Plant has built a plant with a total capacity of 7.5 MW consisting of 5 machines with a capacity of 1.5 MW each. This research is aimed at the appropriate distribution system to be applied there. Medium voltage air duct is one of the existing systems, and is suitable to be applied in Zone II Tanjung Balai Karimun Riau Islands. The cross section size used in the calculated conduit is 100 mm² in the upstream and 16 mm² in the downstream. These conveyors are supported by a pole with a height of 12 m and with a distance between the poles as wide as 100 m. in this system there is also a transformer with a capacity of 160-4000 kVA. This system was tested using ETAP software and produced data that the available generator was not enough to carry the burden in Zone II Tanjung Balai Karimun. Due to inadequate power generation, the long-term solution is to increase the number of plants while the short-term solution is to reduce the burden to be carried.Keywords. SUTM, Sistem Distribusi, ETAP